Inhibition of Orai Channel Function Regulates Mas-Related G Protein-Coupled Receptor-Mediated Responses in Mast Cells - Chaki, Shaswati; Alkanfari, Ibrahim; Roy, Saptarshi; Amponnawarat, Aetas; Hui, Yvonne; Oskeritzian, Carole A.; Ali, Hydar (Frontiers in Immunology, 2022)
Mast cells (MCs) are tissue resident immune cells that play important roles in the pathogenesis of allergic disorders. These responses are mediated via the cross-linking of cell surface high affinity IgE receptor (FcεRI) by antigen resulting in calcium (Ca2+) mobilization, followed by degranulation and release of proinflammatory mediators. In addition to FcεRI, cutaneous MCs express Mas-related G protein-coupled receptor X2 (MRGPRX2; mouse ortholog MrgprB2). Activation of MRGPRX2/B2 by the neuropeptide substance P (SP) is implicated in neurogenic inflammation, chronic urticaria, mastocytosis and atopic dermatitis. Although Ca2+ entry is required for MRGPRX2/B2-mediated MC responses, the possibility that calcium release-activated calcium (CRAC/Orai) channels participate in these responses has not been tested. Lentiviral shRNA-mediated silencing of Orai1, Orai2 or Orai3 in a human MC line (LAD2 cells) resulted in partial inhibition of SP-induced Ca2+ mobilization, degranulation and cytokine/chemokine generation (TNF-α, IL-8 and CCL-3). Synta66, which blocks homo and hetero-dimerization of Orai channels, caused a more robust inhibition of SP-induced responses than knockdown of individual Orai channels. Synta66 also blocked SP-induced extracellular signal-regulated kinase 1/2 (ERK1/2) and Akt phosphorylation and abrogated cytokine/chemokine production. It also inhibited SP-induced Ca2+ mobilization and degranulation in primary human skin MCs and mouse peritoneal MCs. Furthermore, Synta66 attenuated both SP-induced cutaneous vascular permeability and leukocyte recruitment in mouse peritoneum. These findings demonstrate that Orai channels contribute MRGPRX2/B2-mediated MC activation and suggest that their inhibitors could provide a novel approach for the modulation of SP-induced MC/MRGPRX2-mediated disorders.